An up to date on clinical prospects and management of osteoarthritis - Maqbool, Mudasir; Fekadu, Ginenus; Jiang, Xinchan; Bekele, Firomsa; Tolossa, Tadesse; Turi, Ebisa; Fetensa, Getahun; Fanta, Korinan (Annals of medicine and surgery, 2021)
The rising prevalence of osteoarthritis (OA) in the general population has necessitated the development of novel treatment options. It is critical to recognize the joint as a separate entity participating in degenerative processes, as well as the multifaceted nature of OA. OA is incurable because there is currently no medication that can stop or reverse cartilage or bone loss. As this point of view has attracted attention, more research is being directed toward determining how the various joint components are impacted and how they contribute to OA pathogenesis. Over the next few years, several prospective therapies focusing on inflammation, cartilage metabolism, subchondral bone remodelling, cellular senescence, and the peripheral nociceptive pathway are predicted to transform the OA therapy landscape. Stem cell therapies and the use of various biomaterials to target articular cartilage (AC) and osteochondral tissues are now being investigated in considerable detail. Currently, laboratory-made cartilage tissues are on the verge of being used in clinical settings. This review focuses on the update of clinical prospects and management of osteoarthritis, as well as future possibilities for the treatment of OA. •Osteoarthritis (OA) is a general term that incorporates several different joint diseases.•The exact pathophysiology of OA remains unclear.•OA is incurable because there is currently no medication that can stop or reverse cartilage or bone loss.•Nonsteroidal anti-inflammatory drugs are the most frequently prescribed medications to alleviate arthritic discomfort.•Stem cell therapies to target articular cartilage and osteochondral tissues are now under investigation.